Cobalt‐Catalyzed Three‐Component Synthesis of Propargylamine Derivatives and Sonogashira Reaction: A Comparative Study between Co‐NPs and Co‐NHC@MWCNTs. Issue 15 (23rd April 2019) - Hajipour, Abdol R.; Khorsandi, Zahra; Mohammadi, Bahareh
Abstract: Complex of cobalt N‐heterocyclic ligands supported on multi‐walled carbon nanotube (Co‐NHC@MWCNTs) and pure cobalt nanoparticles (Co‐NPs) were synthesized. Their catalytic activities for synthesis of propargylamine derivatives and Sonogashira reaction was explored and compared. All reactions resulted in moderate to excellent yields using these inexpensive and efficient catalysts in green media and mild reaction conditions. Our investigation displayed that the efficiency and reusability of the Co‐NHC@MWCNTs is superior to other (Co‐NPs). Abstract : A novel heterogeneous catalyst has been constructed by modification of multi‐walled CNTs (carbon nanotubes) with NHC complex of cobalt. This catalyst is able to effectively catalyse the three‐component synthesis of propargylamine derivatives and Sonogashira coupling reaction in green and mild temperature with high yields of product in short reaction time.